Cupcake Diaries : Katie Just Desserts - Coco Simon (India Simon Spotlight, 2016)
Katie hasn$1 (Bt seen her father since she was a baby. After so many years apart, her father is trying to make the reunion a happy one, but Katie has a lot of unresolved feelings$1 (Band questions. At the same time Katie is trying to come to grips with her biological dad, her mom$1 (Bs boyfriend tells Katie a secret$1 (Bhe$1 (Bs going to propose to her mom! Will Katie be able to handle all of the big changes in her life?s
Keywords: Realistic Fiction -- Realistic Fiction